2010
DOI: 10.4314/njps.v24i2.52905
|View full text |Cite
|
Sign up to set email alerts
|

The effects of ammonium metavanadate on biochemical hormonal, haematological and histopathological parameters of the female wistar rats

Abstract: Summary:The effects of different doses of Ammonium metavanadate on the biochemical, haematological, hormonal and histopathological parameters of stilbesterol treated female Wistar rats were investigated. Ammonium metavanadate in the dose-range 0-6mg/kg caused a bi-phasic and time-dependent response on the acid (total and prostate) phosphatase.. Furthermore ammonium metavanadate caused a dose-dependent inhibition of the serum alkaline phosphatases. The maximal inhibitory response at 5mg/kg of ammonium metavanad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…There are no reports of either mineralization or degeneration/necrosis of the seminiferous tubules in previous studies 2 , 3 , 4 , 5 , 6 . Vanadium concentrations in the testes with slight to severe mineralization were higher than those in the testes without mineralization, and the testes with mineralization also showed higher calcium and iron concentrations.…”
mentioning
confidence: 87%
See 1 more Smart Citation
“…There are no reports of either mineralization or degeneration/necrosis of the seminiferous tubules in previous studies 2 , 3 , 4 , 5 , 6 . Vanadium concentrations in the testes with slight to severe mineralization were higher than those in the testes without mineralization, and the testes with mineralization also showed higher calcium and iron concentrations.…”
mentioning
confidence: 87%
“…The toxic effects of inorganic V 5+ salts in diabetes model rats include severe diarrhea in life. Histopathologically, hepatocellular necrosis, fatty change and vacuolation, necrosis of renal tubules and necrosis of mucosal epithelial cells in the small intestine have been reported as the toxicities 2 , 3 , 4 , 5 . In addition, testicular toxicity that seems to be related to vanadium-induced oxidative stress during spermatogenesis has been reported 6 .…”
mentioning
confidence: 99%
“…26 Metals such as chromium, cadmium, and iron can alter the hormonal axis indirectly through the generation of oxidative stress. [27][28][29] Obianime et al 30 observed a decrease in the blood levels of Luteinizing Hormone (LH), Follicle Stimulating Hormone (FSH), and prolactin in rats, following intraperitoneal administration of ammonium metavanadate; this decrease in LH and FSH caused by vanadium could explain the low levels of estrogen and progesterone in the blood of exposed mice. In normal mice, the hormones synthesized in the ovary are regulated by the pulses of LH and FSH produced in the anterior pituitary gland; it is possible that vanadium is also interfering in the liberation of these hormones by this gland; however, this hypothesis needs further research to explore this possible explanation.…”
Section: Discussionmentioning
confidence: 99%
“…These free radical scavengers protect the body from such damages only to an extent. Cadmium, like all other heavy metals, has been reported to induce oxidative stress . Oxidative stress contributes to DNA damage and impaired DNA repairing .…”
Section: Introductionmentioning
confidence: 99%